Strategi Dinas Perumahan dan Kawasan Permukiman(PERKIM) dalam Mengatasi Rumah tidak Layak Huni (RTLH) di Kota Bukittinggi - Tiara Amelia Sepna (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The problem of uninhabitable houses (RTLH) is a serious challenge for Bukittinggi City in improving the quality of life of low-income people. This study aims to analyze the strategies implemented by the Housing and Settlement Area Office of Bukittinggi City in tackling RTLH problems. The method used is descriptive qualitative with data collection through interviews, observations, and program documentation. The results showed that the main strategies implemented included a regional budget-based house renovation program, technical assistance to the community, and cross-sectoral coordination with the Health and Social Services Office. These strategies are effective in gradually reducing the number of RTLH, although they still face challenges of limited funds and implementing capacity. Community involvement and strengthening the monitoring system are key to the success and sustainability of the program. This research provides recommendations for developing funding sources, increasing human resource capacity, and optimizing technology in the implementation of the RTLH program in Bukittinggi City.